Cesaŕo Summable Relative Uniform Difference Sequence of Positive Linear Functions - Awad A. Bakery; O. M. Kalthum S. K. Mohamed; Kshetrimayum Renubebeta Devi; Binod Chandra Tripathy (Journal of Function Spaces)
In this article, we introduce the class of sequence of functions C1Δ,ru of Cesaŕo summable relative uniform difference sequence of functions. We have studied the topological properties of C1Δ,ru. We also obtain the necessary and sufficient condition to characterize the matrix classes C1Δ,ru,ℓ∞ru,C1Δ,ru,cru,P.